Technoscapes and mediascapes influence on village and city relations in Manggarai, East Nusa Tenggara - Ans Prawati Yuliantari (SIMULACRA: JURNAL SOSIOLOGI, 2020)
The development of infrastructure and information technology has a significant impact on the relationship between Ruteng, the capital of the Manggarai district, and the surrounding villages. The mobility of the people between the cities and villages has led to new problems which previously did not have a significant influence. The shrinking of the rural agricultural sector and the development of the informal sector in the city are indicative of the dynamic relationship between the two. In order to see the phenomenon of changes that occur in the relationship between Ruteng and the surrounding villages, a theory of landscapes by Arjun Appadurai is used. Interviews were conducted with two entrepreneurs who employed people from five villages, namely Wae Belang, Pong Murung, Purang, Lando, and Nanu, and ten workers from those villages. Observations and literature reviews were carried out to support and complement the data obtained by the interview method. Technoscape, in the form of physical infrastructure development in rural areas and mediascape in the form of television and radio shows, as well as social media, became a pull factor for migration to Ruteng. Meanwhile, the traditional view in the form of go’et (traditional expressions) and the similarity of culture become the push factors for urbanization to Ruteng.